Microfluidic Systems in Cancer Diagnosis: Advancing Exosome and CTC Detection From Laboratory Research to Clinical Application - Bahareh Valinezhad Saghezi; Kamran Mansouri; Rahman Hallaj (Nano Select, 2025)
ABSTRACT This review aims to enable a rapid diagnosis of early‐stage cancer by examining the developments and methods used to collect specific cancer biomarkers, namely, exosomes and circulating tumor cells (CTCs), using microfluidic devices. High throughput, low response time, and accurate control of liquid flow are advantages of microfluidic devices compared to traditional technologies, which often suffer from disadvantages of high cost, time‐consuming procedures, and labor‐intensive processes. Microfluidic‐based approaches have the potential to improve early cancer detection and personalized treatment strategies by efficiently collecting and isolating CTCs and extracellular vesicles (EVs), which provide critical information about cancer progression and the response to treatment. An important step toward leveraging these advances and bringing them to clinical use is ensuring portability to the patient's bedside, that is, integrating point‐of‐care (POC) diagnostics with microfluidic technologies. In this article, we first provide a background on cancer and its markers, cancer biology, and liquid biopsies and their benefits in microfluidic systems in diagnosis. Next, we discuss the importance of the basics of microfluidics, techniques based on it in the detection of EVs and CTCs in advancing cancer research and their benefits, as well as integrating systems POC with microfluidic platforms for bedside applications.